A LARGE MAGNETIC SPECTROMETER SYSTEM FOR HIGH-ENERGY MUON PHYSICS - Allkofer, O; Aubert, J; Bassompierre, G; Becks, K; Bertsch, Y; Besson, C; Best, C; Bohm, E; Botterill, D; Brasse, F; Broll, C; Carr, J; et al. (1981)
The European Muon Collaboration has built a large magnetic spectrometer system for deep inelastic muon scattering experiments at the CERN SPS muon beam. The general characteristics of the apparatus - composed of a target of either liquid hydrogen or deuterium, or iron plus scintillator, followed by a large magnet with wire chambers before and after it for precise angle and momentum measurement, a muon identifier, large trigger hodoscopes, and hadron identifiers - are explained and each part is described in some detail. The main features of the data-acquisition and apparatus-monitoring systems and of the off-line event reconstruction are given. © 1981.